Peripherally tetra-benzimidazole units-substituted zinc(II) phthalocyanines: Synthesis, characterization and investigation of photophysical and photochemical properties - Sen, Pinar; Atmaca, Goknur Yasa; Erdogmus, Ali; Kanmazalp, Sibel Demir; Dege, Necmi; Yildiz, S. Zeki (Elsevier, 2018)
The context of this study is based on the synthesis of 4-(4-(1H-benzo[d] imidazole-2yl) phenoxy group substituted phthalocyanine (4) and 4-(4-(1-allyl-1H-benzo[d] imidazole-2yl) phenoxy group substituted phthalocyanine (5). These phthalocyanine derivatives (4, 5) are reported for the first time with four functional groups containing benzimidazole derivatives that are linked through oxygen bridges to the macrocyclic core. All novel compounds synthesized in this study were fully characterized by general spectroscopic techniques such as FT-IR, UV-vis, H-1 NMR, C-13 NMR, elemental analysis and mass spectroscopy. The compound 4-(4-(1-allyl-1H-benzo[d] imidazole-2yl) phenoxy) phthalonitrile (3) was obtained as single crystal and exact structure of these compounds have also been determined using X-ray diffraction technique at 296 K. Weak intra and intermolecular C-H center dot center dot center dot N interactions and a C-H center dot center dot center dot pi interaction link molecules into a three-dimensional network. Then, spectral, photophysical (fluorescence quantum yields) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of the new complexes were investigated in DMSO solutions. These new phthalocyanines (4 and 5) showed good singlet-oxygen generation (Phi(Delta) = 0.65 for 4 and Phi(Delta) = 0.68 for 5) in DMSO.
Keywords: Synthesis; Metallophthalocyanine; Single crystal; X-ray structure; Fluorescence property; Singlet oxygen; Photodegradation; Photodynamic therapy